Public morality as an object of national security of ukraine: theoretical and legal aspect - Horielova, V.; Горєлова, Вероніка Юріївна (Національний університет "Одеська юридична академія", 2020)
The article examines the expediency of introducing spiritual and moral and ethical values as an object of protection by the National Security Service of Ukraine in accordance with the draft Law on Amendments to the Law of Ukraine “On the Security Service of Ukraine” to improve organizational and legal principles. activities of the Security Service of Ukraine. It is established that as an object of national security, public morality can be interpreted in a narrow and broad sense. In a broad sense, such an object of public morality can be interpreted as a system of state values, such as sovereignty, language, territorial integrity, health, honour, dignity, inviolability of the person and so on. In the narrow sense, the object of social morality is the spiritual state of each individual, because a person according to the Basic Law of Ukraine is the highest value. It is clear that public morality cannot be “programmed” even by interpreting the practice of past world experience, and thus moral values are more appropriate to lay in the legal field to be protected. In our opinion, public morality as an object of protection by the security service of Ukraine should include in its structure values and ideas related to the life of society, as well as requirements and practices corresponding to these values. The current legislation of Ukraine, which is designed to protect human rights and freedoms, unfortunately, does not contain an interpretation of the concept of “morality” and “public morality”. Even though everyone can understand good and evil, useful and harmful, he is also subject to his own ideas of good and bad. Under the law, a basic amount of responsibilities is created, the standard of moral behaviour necessary for the proper functioning of society. Thus, although the law cannot express the will of everyone and cannot correspond to the moral idea of justice of everyone, it is in democratic, legal states that the law creates a personal space of man, in which he harmoniously coexists with his own considerations of morality. Morality as a specific object of the national security service of Ukraine should form a kind of code of appropriate and positive for society, regulate behaviour, have a special spiritual dimension and perform in society several socially significant functions that will promote harmonization of person and society. Although the law cannot express the will of everyone and cannot correspond to the moral notion of justice of everyone, it is in democratic, legal states that the law creates a person’s personal space in which he harmoniously coexists with his own considerations of morality. Morality as a specific object of the national security service of Ukraine should form a kind of code of appropriate and positive for society, regulate behaviour, have a special spiritual dimension and perform in society a number of socially significant functions that will promote harmonization of person and society. Although the law cannot express the will of everyone and cannot correspond to the moral notion of justice of everyone, it is in democratic, legal states that the law creates a person’s personal space in which he harmoniously coexists with his own considerations of morality. Morality as a specific object of the national security service of Ukraine should form a kind of code of appropriate and positive for society, regulate behaviour, have a special spiritual dimension and perform in society a number of socially significant functions that will promote harmonization of person and society
Keywords: public morality; object of national security; human values; principles